Injury accident reporting at a public hospital in the Brazilian Amazon - Sousa, Lirian Raquel Bezerra de (2017)
Objective: To describe the clinical and epidemiological profile of injury accident patients admitted to a public hospital in the Brazilian Amazon. Methods: A cross-sectional study with 588 patients hospitalized during the year 2013 at the Municipal Hospital of Santarém (Pará, Brazil) in result of injury accidents. Sociodemographic and clinical data was collected. Descriptive statistics was adopted for data analysis. Results: Of the patients treated, 75.85% (446) were male, 51.19% (247) in the age group of 19 to 59 years, with road traffic accident as the main cause for 26.02% (153) of the victims. Closed fractures occurred in 50.85% (289) of cases, 77.09% (453) were motorcycle accidents, and the upper limbs were injured in 48.30% (284) of the cases. Conclusion: The profile found showed the predominance of adult men, victims of traffic accidents involving motorcycle, generating closed fracture of the upper limbs, which demands the implementation of actions and policies aimed at accident prevention.